Cannabidiol for the treatment of cannabis withdrawal syndrome: a case report. (24th October 2012) - Crippa, J. A. S.; Hallak, J. E. C.; Machado‐de‐Sousa, J. P.; Queiroz, R. H. C.; Bergamaschi, M.; Chagas, M. H. N.; Zuardi, A. W.
Summary What is known and Objective: Cannabis withdrawal in heavy users is commonly followed by increased anxiety, insomnia, loss of appetite, migraine, irritability, restlessness and other physical and psychological signs. Tolerance to cannabis and cannabis withdrawal symptoms are believed to be the result of the desensitization of CB1 receptors by THC. Case summary: This report describes the case of a 19‐year‐old woman with cannabis withdrawal syndrome treated with cannabidiol (CBD) for 10 days. Daily symptom assessments demonstrated the absence of significant withdrawal, anxiety and dissociative symptoms during the treatment. What is new and Conclusion: CBD can be effective for the treatment of cannabis withdrawal syndrome.